Vascularized Muscle Flap to Reduce Wound Breakdown During Flexible Electrode-Mediated Functional Electrical Stimulation After Peripheral Nerve Injury - McAvoy, Malia; Doloff, Joshua C.; Khan, Omar F.; Rosen, Joseph; Langer, Robert; Anderson, Daniel G. (Frontiers in Neurology, 2020)
The success of devices delivering functional electrical stimulation (FES) has been hindered by complications related to implants including skin breakdown and subsequent wound dehiscence. Our hypothesis was that a vascularized muscle flap along the dorsal surface of an epimysial electrode would prevent skin breakdown during FES therapy to treat atrophy of the gastrocnemius muscle during peripheral nerve injury. Resection of a tibial nerve segment with subsequent electrode implantation on the dorsal surfaces of the gastrocnemius muscle was performed on ten Lewis rats. In five rats, the biceps femoris (BF) muscle was dissected and placed along the dorsal surface of the electrode (Flap group). The other five animals did not undergo flap placement (No Flap group). All animals were treated with daily FES therapy for 2 weeks and degree of immune response and skin breakdown were evaluated. The postoperative course of one animal in the No Flap group was complicated by complete wound dehiscence requiring euthanasia of the animal on postoperative day 4. The remaining 4 No Flap animals showed evidence of ulceration at the implant by postoperative day 7. The 5 animals in the Flap group did not have ulcerative lesions. Excised tissue at postoperative day 14 examined by histology and in vivo Imaging System (IVIS) showed decreased implant-induced inflammation in the Flap group. Expression of specific markers for local foreign body response were also decreased in the Flap group.